Efektivitas Bimbingan Pranikah dalam Menegakkan Maqashid Nikah: Studi di KUA Kecamatan Kute Panang - Noprian Ramadhan; Bukhari Ali; Shabarullah Shabarullah (Lembaga Yasin AlSys, 2026)
The growing potential for marital disharmony arising from low levels of readiness among prospective spouses—mentally, spiritually, and in terms of religious understanding—before entering married life underscores the importance of strengthening premarital counseling at the Kantor Urusan Agama (KUA, Office of Religious Affairs) as an effort to uphold maqāṣid nikah in building a sakinah family. This study aimed to examine the effectiveness of premarital counseling at the KUA of Kute Panang Subdistrict, Aceh Tengah Regency, in realizing maqāṣid nikah as the foundation for a sakinah family. A qualitative approach with field research methods was employed, using in-depth interviews with a marriage registrar (penghulu), religious counselors (penyuluh agama), and three married couples who had participated in premarital counseling. The findings show that the implementation of premarital counseling at the KUA of Kute Panang Subdistrict is effective, as indicated by the appropriateness of the content, the use of lectures and interactive discussions, and its orientation toward instilling Islamic values, spousal responsibilities, and family communication. The impact of premarital counseling is reflected in increased knowledge, attitudes, and religious behavior among prospective spouses, which contributes to the realization of maqāṣid nikah, particularly the protection of religion (ḥifẓ al-dīn), lineage (ḥifẓ al-nasl), and honor (ḥifẓ al-ʿirḍ), thereby fostering families that are sakinah, mawaddah, and raḥmah. Thus, premarital counseling at the KUA of Kute Panang Subdistrict is aligned with maqāṣid al-syarīʿah and reflects the principle of promoting benefit and preventing harm (jalb al-maṣāliḥ wa darʾ al-mafāsid) in the provision of religious services and family guidance.